A Qualitative Study on Women's Experiences of Obesity and Weight Changes Following the Use of Injectable Contraceptives - Angelia Pondaa; Siska Sibua; Cicilia Karlina Lariwu; Grace Aneke Merentek; Ever Mario Lontaan; Finni Fitria Tumiwa; Meilita Enggune; Maryati Agustina Tatangindatu (Gayaku Publisher, 2026)
Background: Three-month injectable contraception is one of the most widely used contraceptive methods in Indonesia due to its practicality and effectiveness. However, long-term use is often associated with weight gain, which may affect women's physical, psychological, and social well-being, as well as the continuation of contraceptive use. Objective: This study aimed to explore the experiences and perceptions of women using three-month injectable contraception regarding weight gain in the working area of Bahu Public Health Center, Malalayang District, Manado City. Methods: This study employed a qualitative design with a phenomenological approach. Data were collected through in-depth interviews with 12 participants selected using purposive sampling. The number of participants was determined based on the principle of data saturation. Data were analyzed to identify themes related to participants’ experiences and perceptions of weight gain during the use of three-month injectable contraception. Results: The findings revealed that most participants experienced weight gain after using three-month injectable contraception. The increase in body weight affected their physical activities, caused feelings of discomfort, reduced self-confidence, and influenced social interactions. Despite these challenges, the majority of participants chose to continue using injectable contraception because they perceived it as practical, effective, and suitable for their family planning needs. Conclusion: Weight gain is a common experience among users of three-month injectable contraception and has physical, psychological, and social impacts. Nevertheless, the perceived benefits of this contraceptive method remain the primary factor supporting its continued use. Suggestion: Healthcare providers are encouraged to strengthen counseling regarding the potential side effects of three-month injectable contraception, provide education on weight management strategies, and conduct regular weight monitoring to enhance users’ comfort, satisfaction, and adherence to contraceptive use.